LEGAL POLICY ON HANDLING CORRUPTION BASED ON MASLAHAH: THE PROBLEM OF DISPARITY IN THE IMPLEMENTATION OF ARTICLE 4 OF LAW OF THE REPUBLIC OF INDONESIA NUMBER 31 OF 1999 - Piet Yardi; Bahrul Ulum; Abdul Halim (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research is motivated by the issue of the effectiveness of witness and victim protection within the Indonesian criminal justice system, which is considered not yet to fully reflect the values of restorative justice nor to be harmoniously integrated into the framework of the national legal system. Although regulatory frameworks have been established through Law Number 13 of 2006 as amended by Law Number 31 of 2014 concerning the Protection of Witnesses and Victims, as well as various regulations related to whistleblower and justice collaborator protection, their implementation continues to face normative and structural weaknesses. The lack of synchronization between the Criminal Procedure Code (KUHAP), the Draft Criminal Procedure Code (RUU KUHAP), and other sectoral regulations has resulted in the suboptimal role of the Witness and Victim Protection Agency (LPSK) in guaranteeing the rights of witnesses, victims, perpetrator-witnesses, and reporters, particularly in criminal cases with broad and organized impacts. From the perspective of maqāṣid al-syarī‘ah and the Pancasila Justice Theory, legal protection for witnesses and victims should not be merely procedural-formal in nature, but must be directed toward the restoration of dignity, the assurance of security, and the comprehensive protection of human rights. This study aims to analyze the regulatory weaknesses in witness and victim protection from the perspective of the criminal justice system and to reconstruct such regulations based on restorative justice values. Employing a normative legal research paradigm combined with conceptual, statutory, and theoretical approaches, this research positions the Pancasila Justice Theory as the grand theory, the Legal System Theory as the middle theory, and the Legal Protection Theory as the applied theory. The findings indicate that regulatory reconstruction is necessary through strengthening the institutional position of LPSK, harmonizing it with the Draft Criminal Procedure Code (RUU KUHAP), and reinforcing the protection of whistleblowers and justice collaborators in a more comprehensive and non-discriminatory manner. This reconstruction is directed toward establishing a witness and victim protection system oriented toward restoration (restorative justice), balanced interests among the parties, and the realization of social justice as mandated by the values of Pancasila and human rights principles.